THE ROLE OF THE GEOGRAPHIC INDICATION CERTIFICATION OF ARABIC COFFEE AS AN EFFORT OF LOCAL FARMERS - Pratiwi, Luh Putu Kirana; Budiasa, Made; Yudiarini, Nyoman (International Journal of Research -GRANTHAALAYAH, 2021)
The demand for coffee in Indonesia is relatively high because Indonesia is the fourth largest coffee producing country in the world. This indicates that there is a change in the lifestyle of world coffee consumers who prioritizes health and environmental sustainability. The development of sustainable coffee farming is carried out by increasing the quality and productivity of the coffee harvest through the Geographical Indication Certification program. The results show that the Geographical Indication Certification Strategy in empowering local farmers is the SO (Strength-Opportunities) Strategy, namely: 1) Making the Geographical Indication area an ecotourism area through the development of integrated arabica coffee-based agribusiness (2) Facilitating and stimulating investment in industrial development directed at increasing competitiveness through fostering improvement in the quality and appearance of products in Arabica coffee and other derivative products. Thus, it is necessary to have consistent quality control from the government so that products received by consumers follow the Geographical Indication label.